RCM 3 Methodology Application to Armored Military Vehicle Cooling System - Filipe Silva (Universidade do Porto, 2021)
The ultimate goal of developing the future of Reliability Centered Maintenance is to introduce the RCM3 methodology, applied in this article to the cooling system of high-performance military armored vehicles fleet, used in current operation theaters. This methodology is not only more advanced and aligned with the international standards for physical asset management and risk management, but also allows users to fully understand and quantify the associated risks, focused on the reliability of the systems. The case study aims to obtain a proposed maintenance plan to the vehicle’s cooling system. Methods such as the distribution of Weibull applied to reliability and Right Censored Data, were used for the calculation of MTBF (Mean Time Between Failures). The results of the study confirm the possibility of using the proposed methodology to evaluate the operational reliability of the high-performance military armored vehicles fleet in any armed forces. The maintenance plan obtained with RCM3 proves to be more suitable and capable of reducing the risk associated with the system failure modes.